Branched-chain Amino Acid Metabolism Is Impaired in Mice and Humans with Alzheimer's Disease (OR27-04-19). (13th June 2019) - Siddik, Md Abu Bakkar; Moghaddam, Masoud Zabet; Hegde, Vijay; Shin, Andrew
Abstract: Objectives: Alzheimer's disease (AD) is an irreversible neurodegenerative disorder that is the third leading cause of mortality in the US. AD brain is mainly characterized by accumulated plaques and tangles and diminished neurotransmitters. AD is strongly associated with type 2 diabetes (T2D). Emerging studies suggest that branched-chain amino acids (BCAAs), the essential amino acids we need to obtain from food, are involved in the pathogenesis of insulin resistance and T2D. In support of this concept, BCAA degradation is impaired in obese and/or diabetic individuals, and BCAA supplementation leads to insulin resistance and perturbed glycemic control. It is currently unknown if similar defective BCAA metabolism exists in AD patients. Since BCAAs along with aromatic amino acids are critical for production and maintenance of brain neurotransmitters, here we tested if BCAA metabolism in liver – an organ with the highest BCAA degradation activity – is impaired in AD. Methods: Eight month-old wildtype or AD transgenic mice were fed a standard chow diet until sacrifice. Serum BCAA levels were measured by BCAA assay, and proteins and genes related to BCAA metabolism in liver were determined by western blot and RT-qPCR, respectively. Serum BCAA profile of healthy or AD individuals were assessed by metabolomics analysis. Results: The activity of branched-chain α-keto acid dehydrogenase (BCKDH), the rate-limiting enzyme in BCAA degradation pathway, in liver was significantly suppressed in AD mice compared to wildtypes as evidenced by the protein expression and its phosphorylated, inactive, state. This is supported by increased hepatic BCKDH Kinase at both protein and gene levels in AD mice. Serum BCAAs and/or their metabolites were higher in both AD mice and humans compared to healthy controls, indicating impaired BCAA metabolism. Conclusions: Our findings suggest that hepatic BCAA catabolism is impaired in AD mice. This may lead to high plasma BCAAs and their metabolites that can potentially contribute to the imbalance of brain neurotransmitters and development of AD or related dementia. A longitudinal assessment of BCAA metabolism will allow us to determine if they play a predictive, diagnostic, and/or causal role in the development of AD. Funding Sources: NIH DK099463, Wylie Briscoe Fund, Texas Tech University.